Dampak Program Desa Mandiri Pangan Terhadap Ketahanan Pangan Dan Kemiskinan Di Kabupaten Aceh Timur - Akhmad Baihaqi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. The purpose of this study to analyze and evaluate the impact of the Village Independent Food Programme (Demapan) through empowerment of poor rural communities in managing and utilizing available resources optimally. The research was conducted in Aceh Timur District in two villages receiver Demapan Program Desa Seunuebok Simpang Banda Alam Subdistrict and Gaseh Sayang Subdistrict of Darul Aman. This study uses quantitative methods, with a purposive sampling sampling of the affinity group (participants) and the non-affinity. The analytical method used is descriptive analysis and statistical tests inferesial. Data used in the descriptive analysis of data scoring is shown in tabular form.The results showed domination of asset for poor households still rely on agricultural land as the main assets. Proportion of household poverty level affinity groups in the village at the beginning of the program at Gaseh Sayang classified in the category of the poor, in 2012 reached 60 percent are in the category of prosperous, less prosperous 13.33 percent and 26.67 percent only enter the category of the poor. Seunebok Simpang village at the beginning of the program is actually 60 per cent included in the category of less prosperous, and 40 percent of categories prosperous. The 2012 program in this village have not been able to improve the welfare of the community, where poor families increased 13.33 percent and 53.33 percent down to family or drops to less prosperous or poor family of 6,67 percent.